Community Empowerment Through Social Entrepreneurship - Ramadhan, Triananda Rizkika; Nurjaman, Asep (Universitas Muhammadiyah Ponorogo, 2025)
This study examines the implementation of community empowerment through social entrepreneurship. This study employs previous research sources as references in its analysis and review process and then uses VosViewer to create a concept map or mapping of commonly studied themes. This study employs an article analysis method that utilizes VosViewer. The process involves gathering articles from previous studies, indexed in the Scopus database, which closely aligns with the research topic of community empowerment through social entrepreneurship. Once we have collected these articles, we will conduct an analysis using VosViewer, which facilitates concept mapping through network and density analyses. This study highlights community empowerment's significance in improving social conditions. The study focuses on the economy, community welfare, and addressing the current challenges and social constraints. The limitations of this study are the lack of previous research or reference sources that study social entrepreneurs specifically and in detail. Several previous research results, which very minimally examine the concept of social entrepreneurship as a means of community empowerment, bear this out.